Psychopathy, temperament, and character dimensions of personality as risk determinants of criminal recidivism in schizophrenia patients. Issue 6 (17th August 2021) - Balcioglu, Yasin Hasan; Kirlioglu Balcioglu, Simge Seren; Oncu, Fatih; Turkcan, Ahmet
Abstract: There is considerable evidence on the role of personality traits in the risk of criminal recidivism among schizophrenia patients, besides conventional risk factors. We evaluated the effects of psychopathy and biopsychosocial personality model on general criminal recidivism in schizophrenia patients. Ninety‐four male DSM‐5 diagnosed schizophrenia patients were recruited and classified into three groups according to the number of offenses since diagnosis: reoffenders ( n  = 32), Initial offenders ( n  = 31), and nonoffenders ( n  = 31). All subjects were evaluated by the Turkish versions of Psychopathy Checklist‐Revised (PCL‐R) and Temperament and Character Inventory‐Revised (TCI‐R). In Reoffenders, all subscale scores of PCL‐R and Novelty seeking were the highest, while Self‐directedness and Cooperativeness were the lowest. PCL‐R Total, Factor 1 and Factor 2 positively correlated with Novelty Seeking, and negatively correlated with Harm Avoidance, Self‐directedness, and Cooperativeness in offender patients. For criminal recidivism in offender patients, high PCL‐R Total and Novelty Seeking, low Harm Avoidance, Self‐directedness, and Cooperativeness, being unmarried, presence of childhood adversity, and younger age at the first offense were found to be significant predictors in univariate analyses; multivariate regression models revealed PCL‐R Total and Persistence as the only significant predictors. These results suggest that certain dimensional personality evaluations combined with potential historical, clinical, and forensic risk factors can be employed in forensic settings to screen offender schizophrenia patients at an increased risk of recidivism and to take necessary precautions against further criminal behavior.